Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2: Literatur Review - Nanda, Vika Ayu; Rudini, Dini; Martawinarti, Rts Netisa; Sulistiawan, Andika; Irwanti Sari , Putri (Jurnal Inovasi Global, 2025)
Diabetes Mellitus (DM) is a chronic disease that requires long-term management and strong social support, particularly from the family. Family support plays a major role in patients’ ability to control the disease, adapt to lifestyle changes, and improve their quality of life. This review aims to examine research findings from the last five years (2020–2025) regarding the relationship between family support and the quality of life of patients with Type II Diabetes Mellitus. Based on an analysis of 15 national and international journals, all studies indicate a significant relationship between the level of family support and the improvement of patients’ quality of life. Emotional, informational, instrumental, and appraisal support are key factors in enhancing treatment adherence and patients’ psychological well-being.